The copper-catalyzed synthesis of dihydrooxazoles from α, β-unsaturated ketoximes and activated ketones. Issue 59 (1st July 2021) - Rong, Binsen; Xu, Gaochen; Yan, Huan; Zhang, Sai; Wu, Qinghuan; Zhu, Ning; Duan, Jindian; Guo, Kai
Abstract : A copper-catalyzed [3+2]-type condensation reaction between α, β-unsaturated ketoximes and activated ketones for the synthesis of dihydrooxazoles is described. Abstract : The first copper-catalyzed [3+2]-type condensation reaction of α, β-unsaturated ketoximes with activated ketones has been described for the synthesis of dihydrooxazoles, especially trifluoromethyl-decorated dihydrooxazoles. Notable features of this method include its broad substrate scope, good functional group tolerance, and simple operation.